2010
DOI: 10.1016/j.adolescence.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Individual and contextual parameters associated with adolescents’ domain specific self‐perceptions

Abstract: The present study examined the role of adolescents’ self‐esteem and perceptions of family and classroom contexts on their domain specific self‐perceptions. 345 Greek junior high school adolescents aged 14–16 completed measures of domain specific self‐perceptions, self‐esteem, parenting styles and classroom climate. Hierarchical regression analyses revealed that both family and classroom contexts predicted students’ self‐perceptions, after students’ demographics, academic achievement and self‐esteem were contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…It may not be as affected by internal interpretations of the conflict as a general evaluation of the self. Instead, scholastic competence seems to be stronger influenced by previous academic achievement (Bouchey and Harter 2005;Kokkinos and Hatzinikolaou 2011). Unfortunately, in our study we do not have information about school grades.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It may not be as affected by internal interpretations of the conflict as a general evaluation of the self. Instead, scholastic competence seems to be stronger influenced by previous academic achievement (Bouchey and Harter 2005;Kokkinos and Hatzinikolaou 2011). Unfortunately, in our study we do not have information about school grades.…”
Section: Discussionmentioning
confidence: 66%
“…This longitudinal study, using adolescents' self-reports, indicated that parenting quality (parental warmth and psychological control) did indeed mediate the link between adolescents' awareness of marital conflict and subsequent decreases in self-esteem. Further studies also indicate positive relationships between parenting quality and adolescents' self-esteem (e.g., Bulanda and Majumdar 2009;Lamborn et al 1991) and scholastic competence (Bronstein et al 2005;Kokkinos and Hatzinikolaou 2011), lending support to the relevancy of the spillover hypothesis in explaining the negative effect of marital conflict on children's self-evaluation.…”
Section: Parenting Qualitymentioning
confidence: 88%
“…The effects of an authoritarian style varied across cultures and contexts (Dehyadegary, Yaacob, Juhari, & Abu, 2012) and thus the preferred level of practicing an authoritarian style might not be clear. This is true especially in the context of comparing collectivistic and individualistic cultures (Hung, 2007;Kokkinos & Hatzinikolaou, 2011) where parenting styles may have different patterns of relationships with children's outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Parental support could promote SE in children and reduce psychological distress by offering their support throughout this developmental phase [23]. In addition, adolescence who receive high parental support has better SE than those who receive low parental support [24,25]. Furthermore, it has been reported that SE is an important mediator between social support and internalizing symptoms in adolescents [26].…”
Section: Introductionmentioning
confidence: 99%